PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN TERHADAP MINAT MENJADI GURU PADA LULUSAN SMA DI KOTA PALEMBANG - Agustina Marzuki; Crystha Armereo; Dian Septianti; Agung Anggoro Seto (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
The purpose of this research is to know the influence of compensation, motivation, and environment on the interest of being a teacher in high school students in Palembang. This type of research is associative. The population of this study was all high school students in Palembang with sampling techniques using accidental sampling with the number of samples determined by 397 respondents. Data analysis techniques using multiple linear regression analyses. The results found that compensation, motivation, and environment have a significant effect on the interest of being teachers in graduate school students in Palembang both simultaneously and partially with a significance value of 0.000. Compensation is the most influential variable with a substantial influence of 53.6%, while motivation and environment have an influence of 43.7% and 27.9% respectively.